2022
DOI: 10.21037/atm-22-5099
|View full text |Cite
|
Sign up to set email alerts
|

The value of the Advanced Lung Cancer Inflammation Index (ALI) in assessing the prognosis of patients with hepatocellular carcinoma treated with camrelizumab: a retrospective cohort study

Abstract: Background: The Advanced Lung Cancer Inflammation Index (ALI) is considered a useful prognostic biomarker for clinical outcome in patients with malignancy. However, the prognostic value of ALI in patients with advanced hepatocellular carcinoma (HCC) is unclear. In this study we assessed the prognostic value of the ALI in patients with HCC treated with camrelizumab.Methods: This retrospective study analyzed patients with advanced hepatocellular carcinoma treated with the ICI, camrelizumab alone or in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Jafri et al, developed an advanced lung cancer inflammation index (ALI) that combined body mass index (BMI) and albumin with NLR 10 . Several studies have corroborated these findings, where low ALI scores are associated with a poor prognosis in various solid tumors (including lung cancer) 11 14 . Valero et al, recently proposed a novel index (Host-Index) that included parameters such as neutrophils, monocytes, hemoglobin, albumin, and lymphocytes.…”
Section: Introductionmentioning
confidence: 73%
“…Jafri et al, developed an advanced lung cancer inflammation index (ALI) that combined body mass index (BMI) and albumin with NLR 10 . Several studies have corroborated these findings, where low ALI scores are associated with a poor prognosis in various solid tumors (including lung cancer) 11 14 . Valero et al, recently proposed a novel index (Host-Index) that included parameters such as neutrophils, monocytes, hemoglobin, albumin, and lymphocytes.…”
Section: Introductionmentioning
confidence: 73%
“…ALI before immunotherapy is a strong predictor for disease control and provides great predictive value for metastatic melanoma patients treated with immunotherapy as second-line therapy ( 25 ). In HCC, ALI was also found to predict HCC survival in patients with advanced HCC receiving immunotherapy ( 13 , 14 ). Nevertheless, the link between ALI, systemic inflammation, and treatment response remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang X showed that preoperative ALI was an independent prognostic factor for GC patients undergoing curative gastrectomy [29]. ALI was also revealed to be a prognostic predictor for EC, liver cancer, and cholangiocarcinoma [30][31][32][33]. However, Pian G, Yin CZ, and Barth DA reported that there was no significant difference between ALI and DFS after gastrointestinal surgery [22,28,34].…”
Section: Discussionmentioning
confidence: 99%
“…Pian G, Yin CZ, and Barth DA et al demonstrated that there was no significant difference in ALI between patients receiving CRC surgery or GC surgery [22,28,34]. Others thought that a low ALI level would lead to a poor prognosis for gastrointestinal cancer patients [21,[23][24][25][26][27][29][30][31][32][33]. Therefore, we aimed to explore the exact prognostic ability of ALI for patients with gastrointestinal cancer undergoing surgery.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation